The old curiosity shop - Dickens, Charles, 1812-1870.; Page, Norman (London ; New York : Penguin Books, 2000)
The sensational bestselling story of Little Nell, the beautiful child thrown into a shadowy, terrifying world, seems to belong less to the history of the Victorian novel than to folklore, fairy tale, or myth. The sorrows of Nell and her grandfather are offset by Dickens's creation of a dazzling contemporary world inhabited by some of his most brilliantly drawn characters-the eloquent ne'er-do-well Dick Swiveller; the hungry maid known as the "Marchioness"; the mannish lawyer Sally Brass; Quilp's brow-beaten mother-in-law; and Quilp himself, the lustful, vengeful dwarf, whose demonic energy makes a vivid counterpoint to Nell's purity.
Includes bibliographical references (p. xix-xxx).
Keywords: Girls -- Fiction; Gamblers -- Fiction; Grandfathers -- Fiction; Antique dealers -- Fiction; Loss (Psychology) -- Fiction; Grandparent and child -- Fiction; England -- Fiction; Didactic fiction; Domestic fiction